Bringing Gender Equality Issues to the Youth in Uzbekistan as a Psychological Problem - Abdullaevna, Bakhramova Abira (International Journal on Integrated Education, 2023)
The article is devoted to the measures taken in Uzbekistan in the last 3 years to ensure gender equality. Gender policy is considered through the prism of building a developed and just society and positive changes in the socio-political life of the country are noted. New laws in Uzbekistan serve to ensure gender equality and are fully in line with international standards. The initiatives of the head of state also play an important role in achieving this goal.